PHYSIOLOGICAL QUALITY OF Syzygium cumini L. SEEDS DURING STORAGE - Oliveira, Lucicléia Mendes de (2015)
http://dx.doi.org/10.5902/1980509820594Syzygium cumini L. is a native Indian tree popularly known as “jambolão”, largely grown as ornamental, medicinal properties and its fruits are edible, however, studies on seed conservation are still insufficient. The objective of this research was to evaluate the physiological quality of Syzygium cumini seeds during storage. The work was performed at the seed testing laboratory and in the greenhouse of the Center for Agricultural Sciences (CCA) of the Federal University of Paraíba (UFPB), Campus II, Areia -PB. The fruits were depulped and the seeds were placed in double plastic bags containing moistened (10 to 20% moisture) substrates: sand, vermiculite and sand+vermiculite (1:1). The plastic bags were stored in a dry chamber (19 ± 5 ºC and 74 ± 20 % RH) for 30 days. Every six days the seeds were removed for the determination of water content and seedling emergence test, emergence speed index, length and dry matter of seedling. The best conditions for the preservation of physiological seed quality of “jambolão” are obtained when seeds are packed in humid substrates (vermiculite and/or sand, vermiculite), and under this condition the seeds stay viable for 30 days. Vermiculite+sand with 10% of moisture stand out as the best treatment to preserve the physiological characteristics.